Apakah permainan gerobak dorong dapat meningkatkan kemampuan melempar bola pada permainan bola basket? - Prasetyo, Rosa; Destriana, Destriana; Segar, David (Lambung Mangkurat University, 2025)
Abstract: This research aims to improve the ability to throw the ball in a basketball game through a wheelbarrow game in class VIII.3 students state junior high school number 16 in the 2024/2025 academic year. This research uses the Classroom Action Research method. The data source for this research is 36 students in class VIII.3 of state junior high school number 16 for the 2024/2025 academic year. Data collection techniques using observation and assessment of learning outcomes in throwing basketball. The data analysis technique used in this research is descriptive, based on quantitative analysis with percentages. Based on the research results, it was found that using the wheelbarrow game can improve the ability to throw the ball in basketball games for class VIII.3 students at state junior high school number 16 for the 2024/2025 academic year. From the results of the analysis, significant improvements were obtained from pre-cycle, cycle I and cycle II. The results of learning to throw the basketball game in the pre-cycle in the complete category were 50% or 18 students. The results of learning to throw the ball in the basketball game in cycle I were in the complete category, namely 75% or 27 students, and the results of learning to throw the ball in the basketball game in cycle II were in the complete category, namely 88% or 32 students. The conclusion of this research is that the wheelbarrow game is effective in improving the ball throwing ability of class VIII.3 students at state junior high school number 16